Covalently Grafting Cobalt Porphyrin onto Carbon Nanotubes for Efficient CO2 Electroreduction. (14th February 2019) - Zhu, Minghui; Chen, Jiacheng; Huang, Libei; Ye, Ruquan; Xu, Jing; Han, Yi‐Fan
Abstract: Molecular complexes with inexpensive transition‐metal centers have drawn extensive attention, as they show a high selectivity in the electrochemical conversion of CO2 to CO. In this work, we propose a new strategy to covalently graft cobalt porphyrin onto the surface of a carbon nanotube by a substitution reaction at the metal center. Material characterization and electrochemical studies reveal that the porphyrin molecules are well dispersed at a high loading of 10 wt. %. As a result, the turnover frequency for CO formation is improved by a factor of three compared to traditional physically‐mixed catalysts with the same cobalt content. This leads to an outstanding overall current density of 25.1 mA cm −2 and a Faradaic efficiency of 98.3 % at 490 mV overpotential with excellent long‐term stability. This work provides an effective pathway for the improvement of the performance of electrocatalysts that could inspire rational design of molecular catalysts in the future. Abstract : Gut verteilt : Durch eine Substitution am Metallzentrum kann Cobaltporphyrin kovalent an Kohlenstoffnanoröhren gebunden werden. Dies führt zu einer deutlichen Effizienzsteigerung in der elektrochemischen Reduktion von CO2 im Vergleich zu Systemen, in denen die beiden Verbindungen nur physikalisch gemischt werden.